A multi-site validation in India of the line probe assay for the rapid diagnosis of multi-drug resistant tuberculosis directly from sputum specimens. - Neeraj Raizada; K S Sachdeva; D S Chauhan; Bharti Malhotra; Kishore Reddy; P V Dave; Yamuna Mundade; Pranav Patel; Ranjani Ramachandran; Ram Das; Rajesh Solanki; Douglas Fraser Wares; et al. (PLoS ONE)
Unlabelled Rifampicin (R) and isoniazid (H) are key first-line anti-tuberculosis drugs. Failure to detect resistance to these two drugs early results in treatment failure and poor clinical outcomes. The study purpose was to validate the use of the GenoType MTBDRplus line probe assay (LPA) to detect resistance to R and H in Mycobacterium tuberculosis strains directly from smear-positive sputum samples in India. Method Smear positive sputum specimens from 320 patients were subjected to LPA and results compared against those from conventional Lowenstein Jensen (LJ) culture and drug susceptibility testing (C&DST). All specimens with discordant R DST results were subjected to either sequencing of the rpoB gene and/or repeat DST on liquid culture (MGIT 960) at a National Reference Laboratory. Results Significantly higher proportion of interpretable results were observed with LPA compared to LJ C&DST (94% vs. 80%, p-value <0.01). A total of 248 patients had both LJ and LPA DST results available; 232 (93.5%) had concordant R DST results. Among the 16 discordant R DST results, 13 (81%) were resolved in agreement with LPA results. Final LPA performance characteristics were sensitivity 96% (CI: 90%-98%), specificity 99% (CI: 95%-99%), positive predictive value 99% (CI: 95%-99%), and negative predictive value 95% (CI: 89%-98%). The median turnaround testing time, including specimen transportation time, on LPA was 11 days as compared with 89 days for LJ C&DST. Conclusions LPA proved highly accurate in the rapid detection of R resistance. The reduction in time to diagnosis may potentially enable earlier commencement of the appropriate drug therapy, leading to some reduction of transmission of drug-resistant strains.